The Polish Version of the Trait Meta-Mood Scale-24 in Adolescents: A Measure of Perceived Emotional Intelligence - Rosario Cabello; Izabela Zych; Vicente J. Llorent; Pablo Fernández-Berrocal (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
The Trait Meta-Mood Scale is widely used to assess individual differences in perceived emotional intelligence. This instrument measures self-reported emotional attention, clarity, and repair. The present study analyzed the psychometric properties including reliability and validity of a Polish version of the TMMS-24 for adolescents including a broad sample of Polish 16 to 22 years old participants (40.3% girls). Results of a confirmatory factor analysis showed that, as its original version, TMMS-24 has a three-factor structure (attention, clarity, and repair), an adequate internal consistency and correlations among the three factors. In terms of relations with other variables, we found evidence of convergent validity with emotional empathy, and discriminant validity with aggressive behavior. These findings suggest that the Polish version of the TMMS-24 for adolescents is a valid instrument for evaluating perceived emotional intelligence in Polish-speaking adolescents that can be used for basic and applied research, and for the evaluation of programs for the promotion of socioemotional competencies.